Penerapan Andragogi Driyarkara dalam Mengatasi Hambatan Komunikasi Antarbudaya Mahasiswa - Wilibrordus Megandika Wicaksono; Monika Gisthi Secaresmi; Julius Novan Deni Kurniawan (CV. ITTC INDONESIA, 2026)
Differences in cultural backgrounds, languages, and communication styles, particularly between students from Java and those from outside Java, create communication barriers in the 2023 Information Systems A class at STIKOM Yos Sudarso. These barriers affect classroom interaction and learning processes among students who come from diverse regions of Indonesia. Segregated seating patterns and suboptimal academic performance further illustrate the dynamics of the class. This study aims to analyze the application of Driyarkara’s andragogical concepts as a strategy to resolve intercultural communication conflicts and to create a more harmonious and effective learning environment. This research employs a qualitative method with data collected through literature review, interviews, group discussions, and reflective video analysis. Data were examined by comparing field findings and student reflections with theoretical frameworks. The results reveal four types of communication barriers: status effects, semantic problems, perceptual distortion, and cultural differences. The application of Driyarkara’s andragogy, emphasizing concrete experience, critical reflection, humanistic dialogue, and active participation, effectively reduces intercultural misunderstandings, enhances collaboration, and fosters a more harmonious, inclusive, and productive classroom atmosphere. In-depth discussions designed to uncover fundamental realities, along with shared reflection, allow students to understand one another’s cultural backgrounds, enabling more effective interpersonal communication. These findings affirm that humanistic and contextual learning approaches are effective in overcoming communication barriers in multicultural settings, particularly within modern higher education institutions